Identification of cell-specific targets of sumoylation during mouse spermatogenesis. Issue 2 (February 2016) - Xiao, Yuxuan; Pollack, Daniel; Andrusier, Miriam; Levy, Avi; Callaway, Myrasol; Nieves, Edward; Reddi, Prabhakara; Vigodner, Margarita
Abstract : Recent findings suggest diverse and potentially multiple roles of small ubiquitin-like modifier (SUMO) in testicular function and spermatogenesis. However, SUMO targets remain uncharacterized in the testis due to the complex multicellular nature of testicular tissue, the inability to maintain and manipulate spermatogenesis in vitro, and the technical challenges involved in identifying low-abundance endogenous SUMO targets. In this study, we performed cell-specific identification of sumoylated proteins using concentrated cell lysates prepared with de-sumoylation inhibitors from freshly purified spermatocytes and spermatids. One-hundred and twenty proteins were uniquely identified in the spermatocyte and/or spermatid fractions. The identified proteins are involved in the regulation of transcription, stress response, microRNA biogenesis, regulation of major enzymatic pathways, nuclear–cytoplasmic transport, cell-cycle control, acrosome biogenesis, and other processes. Several proteins with important roles during spermatogenesis were chosen for further characterization by co-immunoprecipitation, co-localization, and in vitro sumoylation studies. GPS-SUMO Software was used to identify consensus and non-consensus sumoylation sites within the amino acid sequences of the proteins. The analyses confirmed the cell-specific sumoylation and/or SUMO interaction of several novel, previously uncharacterized SUMO targets such as CDK1, RNAP II, CDC5, MILI, DDX4, TDP-43, and STK31. Furthermore, several proteins that were previously identified as SUMO targets in somatic cells (KAP1 and MDC1) were identified as SUMO targets in germ cells. Many of these proteins have a unique role in spermatogenesis and during meiotic progression. This research opens a novel avenue for further studies of SUMO at the level of individual targets.